2015
DOI: 10.1007/s00595-015-1291-3
|View full text |Cite
|
Sign up to set email alerts
|

The advantages of selecting cartridges with a 1.8 mm height for pulmonary stapling

Abstract: The gold cartridge appears to cause the least complications and may therefore be the most appropriate cartridge for stapling the pulmonary parenchyma among the tested staplers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Both of these studies reported similar rates (0.022% and 0.029%). 12,17 The other observational studies excluding these 2 were much smaller and reported a higher incidence (0.3% to 2.3%). 10,[14][15][16][18][19][20] Kwazneski et al 2 performed a prospective survey targeting program directors of minimally invasive specialists.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Both of these studies reported similar rates (0.022% and 0.029%). 12,17 The other observational studies excluding these 2 were much smaller and reported a higher incidence (0.3% to 2.3%). 10,[14][15][16][18][19][20] Kwazneski et al 2 performed a prospective survey targeting program directors of minimally invasive specialists.…”
Section: Resultsmentioning
confidence: 92%
“…2,3,10,[12][13][14][15][16] The lower rates were reported by large multi-institutional retrospective reviews by the same authors. 12,17 They investigated adverse events while stapling pulmonary parenchyma and vasculature during thoracic surgery. Both of these studies reported similar rates (0.022% and 0.029%).…”
Section: Resultsmentioning
confidence: 99%